The Importance of a Whole-of-Department Framework in Learning Partnerships - Hunt, Lynne Yvonne Anne; Hunt, Lyall John (International Journal for Students as Partners, 2017)
This historical case study of the Yilgarn Project explores a community-engaged, whole-of-department framework that involved students as partners in research and publications. It shows how existing flexible curriculum and assessment processes enabled student engagement with research. The purpose of this case study is to share practice and to explore partnership styles. It locates partnership approaches in the intellectual traditions from which they have emerged and explores the relative importance of the process of partnership as well as the product, which is described in terms of the skills that students learned. The Yilgarn Project is analysed in the context of the Higher Education Academy (HEA) Framework (2014) with special reference to the core values that inform partnerships. This gives rise to discussion of the nature of partnership and the relative importance of using empowering processes to enhance student learning outcomes.